Next-generation Enem assessment with fewer items and high reliability using CAT - Alexandre Jaloto; Ricardo Primi (Estudos em Avaliação Educacional)
The Exame Nacional do Ensino Médio [Brazilian High School Exam] (Enem) is a test that includes an essay and four 45-item tests. Its reliability and the impact of fatigue on scores are important considerations, so Computerized Adaptive Testing (CAT) may be a way to address these issues. Therefore, the present study aimed to verify the possibility of reducing the number of items on the Enem, using a CAT. We used tests from the 2009 to 2019 editions of the Enem. We simulated a CAT, which ended when the error was less than 0.30, or when 45 items were applied. On average, the application ranged from 12.0 (Languages and Codes – LC) to 29.2 (Mathematics – MT) items. The results point to the potential of reducing the size of the Enem to 20 items for a proportion that varies from 39.8% (MT) to 94.8% (LC) of the population.